2009
DOI: 10.1007/s11071-009-9569-x
|View full text |Cite
|
Sign up to set email alerts
|

Weakly coupled parametrically forced oscillator networks: existence, stability, and symmetry of solutions

Abstract: In this paper, we discuss existence, stability, and symmetry of solutions for networks of parametrically forced oscillators. We consider a nonlinear oscillator model with strong 2:1 resonance via parametric excitation. For uncoupled systems, the 2:1 resonance property results in sets of solutions that we classify using a combinatorial approach. The symmetry properties for solution sets are presented as are the group operators that generate the isotropy subgroups. We then impose weak coupling and prove that sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Dynamic vibration absorber is a typical mechanical model described by (1) [1,2] (in this case m is usually much larger than m e ). Dynamics of coupled periodically driven oscillators is very complicated [3][4][5][6][7][8][9][10][11][12][13]. It is important that experimental study confirms good agreement with theoretical model [6].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Dynamic vibration absorber is a typical mechanical model described by (1) [1,2] (in this case m is usually much larger than m e ). Dynamics of coupled periodically driven oscillators is very complicated [3][4][5][6][7][8][9][10][11][12][13]. It is important that experimental study confirms good agreement with theoretical model [6].…”
Section: Introductionmentioning
confidence: 82%
“…[20] the author outlined a programme to "define and find different branches intersecting at singular points" in onedegree-of-freedom non-linear system and considered also general non-linear dynamical systems. Independently, the Implicit Function Theorem was also successfully applied to bifurcation problems in systems of coupled parametrically forced oscillators in [10]. The authors demonstrated that "provided the periodic orbits for the uncoupled system are hyperbolic, there will be periodic orbits for the weakly coupled system close to the periodic states identified for the uncoupled system" [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Danzl and Moehlis [26] considered networks of nonlinear parametrically forced oscillators with weak coupling, used the implicit function theorem to prove the persistence of the uncoupled solution classes, and investigated this numerically. Far from the weak coupling limit, interesting dynamics such as antisynchronized chaotic behavior were found.…”
Section: Introductionmentioning
confidence: 99%
“…The current paper shares with [26] an emphasis on symmetries and the assumption of weak coupling and with [23,24] an interest in the effect of the forcing phases. As in [23], we utilize a bifurcation theory (unfolding) approach.…”
Section: Introductionmentioning
confidence: 99%